### Brain Teasers

# (6 ? 3)

Can you replace the question marks with math symbols and make the equation correct:

(6 ? 3) ? 2 ? (4 ? 3) = 6

(6 ? 3) ? 2 ? (4 ? 3) = 6

### Answer

(6 + 3) * 2 - (4 * 3) = 6or

(6 - 3) * 2 * (4 - 3) = 6

or

(6 - 3) + 2 + (4 - 3) = 6.

Hide Answer Show Answer

© Kevin Stone: www.brainbashers.com

## What Next?

View a Similar Brain Teaser...

If you become a registered user you can vote on this brain teaser, keep track of which ones you have seen, and even make your own.

### Solve a Puzzle

## Comments

Jan 24, 2002

...

or

(6 + 3) - 2 - (4 - 3) = 6

or

(6 + 3) - 2 - (4 - 3) = 6

Well there are many ways to do this one i just used those 3.

To post a comment, please create an account and sign in.

## Follow Braingle!